2007
DOI: 10.1007/s10482-007-9154-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Campylobacter spp. in poultry and poultry products for sale on the Bulgarian retail market

Abstract: The aim of this study was to investigate the presence of Campylobacter spp. in poultry and poultry products available for the consumers at retail markets in Bulgaria. Samples (n = 210) of poultry carcasses and poultry products for sale at the retail market in Bulgaria were analysed for the presence of Campylobacter spp., of these 35 frozen whole carcasses, 135 chilled poultry cuts (45 wing cuts, 45 thigh cuts and 45 fillet) and 40 thermally treated (ready-to-eat) poultry products. The results obtained showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…A similar finding to what was observed in this study was reported in Bulgaria in which 35.2% of frozen poultry carcasses were contaminated by Campylobacter spp. with high percentages of 91.1% and 88.9% detected in the wing and thigh cuts, respectively [39]. Further, our results are supported by a study done in California USA in which the authors found a higher contamination with Campylobacter jejuni of chicken wings purchased from retail outlets on the day of arrival at the supermarket [50].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar finding to what was observed in this study was reported in Bulgaria in which 35.2% of frozen poultry carcasses were contaminated by Campylobacter spp. with high percentages of 91.1% and 88.9% detected in the wing and thigh cuts, respectively [39]. Further, our results are supported by a study done in California USA in which the authors found a higher contamination with Campylobacter jejuni of chicken wings purchased from retail outlets on the day of arrival at the supermarket [50].…”
Section: Discussionsupporting
confidence: 85%
“…Low prevalence's of retail poultry contamination with Campylobacter spp. have been reported in Brazil 47.5%; [35], Japan 45.8%; [36], Chile 45% [37], USA 41.0% [38] and in Bulgaria 35.2% [39]. Some years back Lee et al [40] showed that C. Jejuni was able to survive for up to almost two months under frozen storage at -20ºC, which is the temperature found in most domestic freezers.…”
Section: Discussionmentioning
confidence: 99%
“…Because of wide distribution of these organisms in healthy animals, Campylobacter are ubiquitously shed into the environment, and the infections can easily access the food chain. However, activities related to chickens rearing, chicken meat processing, and consumption of undercooked meat easily predispose an individual to Campylobacter infection (Stoyanchev et al 2007;Horrocks et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Sterile Preston broth (HiMedia, India, M899) supplemented with selective supplement (HiMedia, India FD-042) containing polymyxin B (5 IU/mL), rifampicin (10 µg/mL), trimethoprim 10 (µg/mL) and cycloheximide (100 µg/mL) along with 10% horse blood (Haffkine Biopharmaceutical Ltd, Pune) was used as enrichment broth. Then one loopful of enrichment broth was streaked onto mCCDA agar plates (ISO, 10272-1;Stoyanchev et al, 2007;Habib et al, 2011). For qualitative analysis, about 0.5 g of caecal contents were directly plated on mCCDA plates (Hansson et al, 2010) Both sets of mCCDA plates were then incubated at 42 ± 1°C for 24 h under microaerobic conditions using McIntosh and Filde's anaerobic jar (Hi-Media, IndiaAnaerobic System Mark VI, LE013).…”
Section: Determination Of Sample Sizementioning
confidence: 99%
“…In countries where frozen or chilled poultry is predominantly consumed, rates of isolation of thermophilic Campylobacters from carcasses were: 49.5% in Spain (Domínguez et al, 2002), 35.2% in Bulgaria (Stoyanchev et al, 2007), 44% Germany (Näther et al, 2009) and 52.5% in the US (Son et al, 2007). The rates of isolation of Campylobacter contamination are higher in countries with traditional "pluck shop" based wet markets: 63% in Iran (Taremi et al, 2006), 68.3% in Korea (Han et al, 2007) and 83.9% in Trinidad.…”
Section: Prevalence Of Campylobacter In Retail Poultry Meat From "Plumentioning
confidence: 99%